2009
DOI: 10.1080/07294360903067013
|View full text |Cite
|
Sign up to set email alerts
|

The relative effects of university success courses and individualized interventions for students with learning disabilities

Abstract: Little is known about the relative effects of post-secondary learning services for students with learning disabilities. We compared outcomes for students with learning disabilities who selected to: (1) take an academic learning success course (course-intervention), (2) have regular individual interventions (high-intervention) or (3) use services only as needed (low-intervention). Pre-and post-test comparisons revealed improvements in academic self-efficacy and academic resourcefulness for students in the cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 28 publications
0
26
0
2
Order By: Relevance
“…Others try to make more visible the services that are already offered [4]; [18] and help the students make a better use of the services they are offered [15]. Integrating the regular and the adapted systems [6], [11], [14] and maximising the opportunities of interaction with their pairs would entail academic success [7], [16], [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others try to make more visible the services that are already offered [4]; [18] and help the students make a better use of the services they are offered [15]. Integrating the regular and the adapted systems [6], [11], [14] and maximising the opportunities of interaction with their pairs would entail academic success [7], [16], [17].…”
Section: Discussionmentioning
confidence: 99%
“…To help students with special needs be prepared to follow a post-secondary education, researchers [15] have studied the effects of academic learning success during secondary school in groups of post secondary students with learning disabilities receiving appropriate services. Three conditions were observed: follow an academic learning success course, benefit from an individual follow-up (highintervention), or an occasional follow-up (lowintervention).…”
Section: Transitionsmentioning
confidence: 99%
“…SWDs oftentimes perceive themselves as unprepared for the increased rigor of HEIs; as a result, they are frequently challenged in both their transition to HEIs and in their retention to complete a degree or certificate (Hilary, 2006). This can lead to anxiety and difficulties with academic expectations leading to decreased retention rates (Connor, 2012;Reed, Kennett, Lewis, Lund -Lucas, Stallberg and Newbold, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Students with disabilities oftentimes perceive themselves as unprepared for the increased rigor of higher education. This can lead to anxiety and difficulties with academic expectations which can all lead to decreased retention rates [13] [14] and they suggested that self-advocacy skills would address the issue. Again they stated that self-advocacy includes having a concept of purpose, thorough goal setting, plan development, being able to articulate personal learning needs, and persistence despite challenges.…”
Section: The Lack Of Self-advocacy Skills and Its Consequencesmentioning
confidence: 99%